Kinematic study of the parsec-scale jet of the quasar PKS 1741–03. Issue 1 (21st April 2014) - Caproni, A.; Melo, I. Tosta e; Abraham, Z.; Monteiro, H.; Roland, J.
Abstract : We present 23 interferometric images of the parsec-scale jet of the quasar PKS 1741–03 at 15, 24 and 43 GHz, spanning about 13 yr. We model the images as a superposition of discrete two-dimensional elliptical Gaussian components, with parameters determined by the cross-entropy technique. All the images present a spatially unresolved component (core) and usually two or three components receding from it. The same components were found in simultaneous 24- and 43-GHz maps, showing the robustness of our model fitting. The core-shift opacity effect between these frequencies is weak. We have identified seven components moving along straight lines at constant apparent superluminal speeds (3.5 ≲ βobs ≲ 6.1), with different sky position angles (−186° ≲ η ≲ −125°). The core flux density tracks quite well the fluctuations seen in the historical single-dish light curve at 14.5 GHz, with no measurable delay. The total flux density from the moving jet components is delayed ∼2 yr in relation to the core light curve, roughly the same as the lag between the ejection epoch and the maximum flux density in the light curves of the jet components. We propose that there are three non-exclusive mechanisms for producing these delays. From the kinematics of the most robust jet components and the core brightness temperature, we determined the bulk Lorentz factor (4.8 ≲ γ ≲ 24.5) and the jet viewing angle ($0{^{°}_{.}} 35 \lesssim θ \lesssim 4{^{°}_{.}} 2$ ); these values agree with previous estimates from the spectral energy distribution of PKS 1741–03 and its radio variability.